2020
DOI: 10.21608/mjae.2020.101818
|View full text |Cite
|
Sign up to set email alerts
|

Water Saving With the Use of Different Irrigation Systems Under Egyptian Conditions

Abstract: The performance of three different irrigation systems (drip, sub-surface and sprinkler irrigation) in terms of actual irrigation water requirements, crop yield, water use efficiency and water saving was experimentally investigated under condition of sugar-beet planting in sandy soil. Water saving through the use of the three irrigation systems was studied as a function of change in water regime (100, 75 and 50%) and planting dates (1 Oct., 20 Oct. and 10 Nov.). Water saving was also recorded in the case of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
3
0
0
Order By: Relevance
“…This indicated that water salinity has a significant impact on WUE. These effects are consistent with those obtained using the same method by Mahmoud and Aboushal 2007, Hajibaland et al 2009, Morad et al 2012.…”
Section: Sugar Yieldsupporting
confidence: 92%
See 2 more Smart Citations
“…This indicated that water salinity has a significant impact on WUE. These effects are consistent with those obtained using the same method by Mahmoud and Aboushal 2007, Hajibaland et al 2009, Morad et al 2012.…”
Section: Sugar Yieldsupporting
confidence: 92%
“…However, the yield increased as the water volume increased (the maximum, intermediate, and lowest sugar yields were 4.817, 4.791, and 3.812 t/fed irrigated by 2500, 3250, and 1750 m³/fed/season, respectively). These results are consistent with those obtained by Morad et al 2012, Moursi and Darwesh 2014, Masri et al 2015, El Darder et al 2017 The interactions between the water irrigation treatment conditions (irrigation system, salinity level, and quantity of water) were highly significant for the interactions considered in this examination of sugar yield/fed.…”
Section: Sugar Yieldsupporting
confidence: 91%
See 1 more Smart Citation